Surveillance after surgery for pancreatic cancer : a global scoping review of guidelines and a nordic Survey of contemporary practice - Ansari, Daniel; Søreide, Kjetil; Andersson, Bodil; Hansen, Carsten Palnæs; Seppänen, Hanna; Sparrelid, Ernesto; Labori, Knut Jørgen; Kirkegård, Jakob; Kauhanen, Saila; Månsson, Christopher; Nymo, Linn Såve; Nortunen, Minna; et al. (Taylor & Francis, 2025)
Objectives: Most patients with pancreatic cancer who have undergone surgical resection eventually develop disease recurrence. ‍This study aimed to investigate whether there is evidence to support routine surveillance after pancreatic cancer surgery, with a secondary aim of analyzing the implementation of surveillance strategies in the Nordic countries.
Materials and methods: A scoping review was conducted to identify clinical practice guidelines globally and research studies relating to surveillance after pancreatic cancer resection. This was followed by a survey among 20 pancreatic units from four Nordic countries to assess their current practice of follow-up for operated patients.
Results: Altogether 16 clinical practice guidelines and 17 research studies were included. The guidelines provided inconsistent recommendations regarding postoperative surveillance of pancreatic cancer. The clinical research data were mainly based on retrospective cohort studies with low level of evidence and lead-time bias was not addressed. Active surveillance was recommended in Sweden and Denmark, but not in Norway beyond the post-operative/adjuvant period. Finland had no national recommendations for surveillance. The Nordic survey revealed a wide variation in reported practice among the different units. About 75% (15 of 20 units) performed routine postoperative surveillance. Routine CA 19-9 testing was used by 80% and routine CT by 67% as part of surveillance. About 73% of centers continued follow-up until 5 years postoperatively.
Conclusion: Evidence for routine long-term (i.e. 5 years) surveillance after pancreatic cancer surgery remains limited. Most pancreatic units in the Nordic countries conduct regular follow-up, but protocols vary.